Living the Values: Management of Religious Culture and Student Character Development in Public Schools - Riska Mahalila; Edi Kurniawan Farid; Sollah Solehudin (Journal of Educational Management Research, 2026)
This study aims to analyze the management of religious organizational culture development in improving students’ character. This research employed a qualitative case study approach. Data were collected through interviews, observations, and documentation involving the principal, teachers, students, and parents. Data analysis followed the Miles and Huberman model, including data condensation, data display, and conclusion drawing and verification. The findings revealed that the development of religious organizational culture was implemented through four management functions proposed by George R. Terry, namely planning, organizing, implementation, and evaluation. Planning involved formulating religious programs and implementation strategies, organizing focused on assigning roles and responsibilities to school members, implementation was carried out through religious habituation activities such as congregational Dhuha prayer, recitation of Asmaul Husna, Qur’anic reading, and collective prayers, while evaluation was conducted continuously to monitor program effectiveness and identify areas for improvement. The study found that religious organizational culture contributed significantly to the development of students’ religiosity, discipline, responsibility, and respectful behavior. These findings imply that systematic and sustainable management of religious organizational culture can serve as an effective strategy for strengthening character education and fostering positive student behavior in educational institutions.